Elementary and middle school students’ school attitudes and extracurricular activities - Şeker, Hasan (Revija za elementarno izobraževanje, 2020)
The study aims to determine elementary and middle school students’ school attitudes. A school attitudes measurement tool was used in the study. The participants of the study comprised 410 students. The results of the current study show that willing participation in school activities affects school attitudes. The results also show that with increasing grade level, the rate of willing participation drops. It was also found that there is a significant correlation with participation in extracurricular activities. The school attitudes mean score of students willingly participating in extracurricular activities is significantly higher than that of students participating involuntarily.
Keywords: activities, elementary school, middle school, school attitudes, student participation, willing participation